Turkey the quest for identity - Ahmad, Feroz
This concise history tells the story of Turkey, a country caught between the ideologies of East and West. Feroz Ahmad provides a full survey of Turkey''s checkered past, from its beginnings as a disparate group of tribes to its status as the first secular republic in the Islamic world. In addition to providing a detailed account of the key cultural, economic, and social events, this accessible text also examines the problems faced by modern Turkey, from the rise of Islamic militancy to the current tension in Turkey''s government